WEB-BASED INTERACTIVE EDOM TO IMPROVE THE PERFORMANCE OF UNISBA BLITAR FKIP LECTURERS - Moch Yusuf Zen; Muhammad Iqbal Baihaqi (JOSAR (Journal of Students Academic Research), 2021)
This research aims to improve the lecturers' performance of FKIP UNISBA Blitar through the development of Web-Based Interactive EDOM. This is a transformation from the EDOM based paper that has been applied so far, which is considered biased and not appropriate to be applied with the times. The difference between this Interactive EDOM and online EDOM in general is that there is a discussion forum on the account of each lecturer. So lecturers and students can communicate with each other regarding the evaluation of teaching and learning that has been taken in one semester to improve the quality of teaching and learning in the following semester. The method used in this research is Research and Development (research development) with stages; (1) needs analysis and needs assessment, (2) developing media, (3) expert validation, (4) first revision, (5) try-out, (6) second revision, and (7) final product. Involving 2 experts (experts), namely experts in the field of Information Technology by 80% stated valid and 77% valid experts in the field of educational evaluation. The product produced from this study is the Web- based Interactive EDOM using the Edmodo application with the following description: Interactive EDOM consists of multiple choices and The entries between one student and another student are Lecturers in the intended account are encouraged to interact, respond, clarify, fix related EDOM. Each lecturer at FKIP UNISBA Blitar has 1 account in the Interactive EDOM Each student entry will be directly entered into the intended lecturer There is an absence of Interactive EDOM for students whose names are kept The lecturer account will only be visited by students who meet face to face in that semester.